Settlement of Criminal Acts of Ordinary Abuse Committed by Children - Hibu, Bertelomeus (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study analyzes the model for resolving ordinary child abuse cases committed by children as perpetrators through a restorative justice approach. The urgency of this research is based on the fact that handling children's cases through formal justice channels tends to be retributive, which risks causing stigmatization and psychological trauma for children's future development. The main focus of this research is to evaluate the implementation of the diversion mechanism as an instrument for protecting children's rights in the Indonesian legal system. The research method used is normative legal research with a statute approach and a conceptual approach. Primary legal materials are sourced from the Criminal Code (KUHP) and Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (SPPA). Data analysis was conducted using a descriptive qualitative approach to provide a comprehensive overview of the out-of-court case resolution mechanism. The results of the study indicate that ordinary child abuse cases regulated in Article 351 of the Criminal Code must be resolved through a diversion mechanism at all levels of justice, considering that the penalty is less than seven years. This model prioritizes deliberation involving the perpetrator, victim, and community to achieve restoration of the original state.